EFFECT OF INTRA-ARTERIAL NIMODIPINE ON SUBARACHNOID HEMORRHAGE INJURED BRAIN - Bushinoska, Jasna M.; Chaparoski, Aleksandar; Dodevski, Ace; Bushinoska-Ivanova, Gabriela; Ognjenovic, Ljubomir; Asani, Elmedina; Zafirova, Dina; Vesova, Marija (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Subarachnoid hemorrhage is a pathological condition of the brain, caused by rupture of intracerebral aneurism or arteriovenous malformation, with high morbidity and mortality rate. SAH may conceive permanent brain damage with persistent disability. Vasospasm is the most characteristic pathological state of the vasculature, whose development coincides with onset of bleeding with asymptomatic presentation. The critical extend as a risk factor presents with symptom presentation and indication of brain damage development. Early vasospasm treatment is a priority in prevention of brain ischemia and disability. Existing methods of vasospasm treatment are conservative, endovascular and combined, with simultaneous intraarterial vasodilator application. The aim of this study is to determine whether intraarterial application of Calcium- blocker Nimodipine will generate immediate vasodilation, facilitating endovascular aneurism treatment, resulting in long term resolution of the condition. Fifteen patients with SAH received endovascular treatment in the first 48 hours of hemorrhage onset, with consequent intraarterial Nimodipine application if vasospasm was detected. All patients had ruptured aneurism of anterior circulation. Vessel diameter was measured before and after Nimodipine application. The occurrence and degree of vasodilation, as a difference between both diameters, were considered a confirmation of drug effectiveness.    Complete spasm relief occurred in 10 patients, residual vasospasm persisted in 4 patients, no VS relief occurred in 1 patient.    Intraarterial Nimodipine application during endovascular brain aneurism treatment effectively relieves vasospasm. Early coiling reduces complication risks and development of post ischemic brain damage. Key words: Vasospasm, SAH, Nimodipine, Intraarterial, endovascular treatment.